(untitled) (Revista Electrónica REDINE, 2018)
This article has been prepared for the purpose of publicizing important aspects of managerial action in the context of organizational change. A partial synthesis of the abundant literature on this topic is presented. Different authors point out that the approach is general, so the discussion is made on the knowledge and experience that can be applied to various types of organizations. The management action has a component that identifies with his studies. Being the subject of managerial action, or business management, management theorists have developed studies that have contributed to the role of managers in this case Henry Fayol (French industrial) wrote that managers perform five basic functions: planning will organize, organize, coordinate and control, on his experience as president of a mining industry, began to analyze the issues that make a manager to succeed in management.